PENGARUH WORD OF MOUTH, DESTINATION IMAGE, DAN DESTINATION BRANDIG TERHADAP MINAT BERKUNJUNG KEMBALI DI WISATA PANTAI PASIR PUTIH TUBAN - Siti Mariyam; M. Hufron; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to analyze the Word Of Mouth, Destination Image, and Destination Branding of Revisiting Interest in Tuban White Sand Beach Tour either simultaneously or partially. This research uses an explanatory research type with a quantitative approach. The population in this study were visitors from the White Sand Beach Tourism. Samples taken were 73 respondents. The sampling technique used was snowball. Data were analyzed using multiple linear regression analysis processed with SPSS 16.0 software. The data collection method used was a questionnaire. The results showed that the Word Of Mouth, Destination Image, and Destination Branding simultaneously had a significant effect on Visiting Interest. And Word Of Mouth has a partially significant effect on interest in visiting. Meanwhile, Destination Image has no partially significant effect on Returning Interest. And Destination Branding partially significant effect on Returning Interest. Keywords: Word of Mouth, Destination Image and, Destination Branding for Returning Interest